Effect of the high-density polyethylene melt index on the microcellular foaming of high-density polyethylene/polypropylene blends - Rachtanapun P. (2014)
The effect of high-density polyethylene (HDPE)/polypropylene (PP) blending on the crystallinity as a function of the HDPE melt index was studied. The melting temperature and total amount of crystallinity in the HDPE/PP blends were lower than those of the pure polymers, regardless of the blend composition and melt index. The effects of the melt index, blending, and foaming conditions (foaming temperature and foaming time) on the void fractions of HDPEs of various melt indices and HDPE/PP blends were also investigated. The void fraction was strongly dependent on the foaming time, foaming temperature, and blend composition as well as the melt index of HDPE. The void fraction of the foamed 30:70 HDPE/PP blend was always higher than that of the foamed 50:50 HDPE/PP blend, regardless of the melt index. The microcellular structure could be greatly improved with a suitable ratio of HDPE to PP and with foaming above the melting temperature for long enough; however, using high-meltindex HDPE in the HDPE/PP blends had a deleterious effect on both the void fraction and cell morphology of the blends. © 2004 Wiley Periodicals, Inc.